DIGITAL EDUCATION REVOLUTION : THE IMPACT OF MOODLE-BASED E-CLASS ON STUDENT ACHIEVEMENT - Akhsan, Ibnu Nur; Wibawa, Basuki; Situmorang, Robinson; Siregar, Eveline (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2024)
The learning methods in Vocational High Schools (SMK) have undergone significant changes. These changes were made because the education system needs to adapt to the conditions of society during the COVID-19 pandemic. SMKN 8 Bandung has implemented a blended learning system with 50% offline and 50% online learning. To maximize the teaching and learning process, the school has developed a Webmoodle application to aid student learning. This research aims to determine students' responses to using e-class and WhatsApp as learning media and to assess the improvement in student learning outcomes through the implementation of Webmoodle-based learning media. This study uses a quantitative approach with a quasi-experimental method, employing a nonequivalent control group design with pre-test and post-test. The results of this study show that e-class learning media is superior to WhatsApp. Nonetheless, both e-class and WhatsApp can effectively enhance student learning outcomes.